Compliance with food safety measures and their economic impact on smallholder dairy farmers: Evidence from the Indo-Gangetic plains of India - Katoch, Sonali; Kumar, Anjani; Kolady, Deepthi E.; Sharma, Kriti (Elsevier, 2024)
This study examines the adoption and economic impact of compliance with food safety measures (FSM) using cross-sectional farm-level data from three key states in the Indo-Gangetic Plains, Bihar, Punjab, and Uttar Pradesh, in 2023. The majority of the farmers were operating on marginal and small plots. A Food Safety Index (FSI) derived from 71 distinct practices was used as a quantitative measure of adoption of compliance with FSM. The study assigns 0.60, 0.23, and 0.17 wt to microbiological, physical, and chemical safety measures, respectively, to derive FSI. Determinants of compliance with FSM were analysed using multiple linear regression and ordered logistic model, while Generalized propensity score (GPS) was used to assess the economic impact of compliance with FSM on farm-level performance indicators. The findings indicate that farmers are adopting a moderate level (0.48–0.58) of the FSI. Various socio-economic and demographic factors, such as education, income, marketing channel, training exposure, awareness level, and infrastructure, significantly influence the adoption of FSM. The impact assessment reveals that compliance with FSM correlates with milk prices, productivity, and profitability. However, a lower level of compliance may not yield significant improvements in milk productivity. The study suggests incentivization through pricing reforms, improving infrastructure, strengthening formal marketing channels, and raising awareness through training.